Penerapan Algoritma Adaptive Iterative Dose Reduction 3D (AIDR 3D) dalam Meningkatkan Kualitas Citra pada Pemeriksaan CT Coronary Angiography - Alfisna Fajru Rohmah; Bagus Abimanyu; Edy Susanto (Jurnal Imejing Diagnostik (JImeD), 2024)
Background: CT Coronary Angiography (CTCA) is a non-invasive imaging modality with a high spatial and temporal resolution to diagnose coronary vascular disease. FBP (Filtered Back Projection) has limitations in improving the image quality, so iterative reconstruction is used on CTCA. Adaptive Iterative Dose Reduction (AIDR 3D) is one of the iterative reconstructions developed by Toshiba, which has three levels of strength: mild, standard, and strong. The study aimed to explain the application of AIDR 3D in improving image quality on coronary CT angiography examination. Methods: This research is descriptive with a literature study approach, using articles from NCBI, Science Direct, and Google Scholar. The keywords used are CT Coronary Angiography, AIDR 3D, and Image Quality. The articles obtained are reduced based on inclusion and exclusion criteria so that seven relevant articles are conducted for extraction.Results: The results showed that AIDR 3D could improve the quality of CTCA images with the most significant percentage in AIDR 3D strong by reducing noise 18-46.1% and increasing SNR 21-84.7% and CNR 21-82.2%.Conclusions: The application of AIDR 3D strong in obese patients with CTCA is good to use with standard kVp and 250-450 mA without increasing mA so that it does not increase the dose. AIDR 3D strong can also be used in patients with normal body mass with tube current adjusted according to the patient's body mass if there is no indication on the right coronary artery. AIDR 3D standard can be used in overweight patients and normal body mass.